Antibiofilm Activity of Intracellular Extracts of Westiellopsis prolifica Isolated From Local Environment in Baghdad - Shurooq Latif Al-Tmimi (Journal of Global Pharma Technology, 2018)
Acetone and hexane extracts of cyanobacteria Westiellopsis prolifica was tested In vitro. Antibiofilm activity was evaluated by biofilm production assay against six pathogenic bacteria in which three are Gram- positive bacteria